The Role of Fintech in Transforming Traditional Financial Services - Harsono, Iwan; Suprapti, Ida Ayu Putri (Penelitian dan Pengembangan Ilmu, 2024)
This research explores the role of Fintech in changing traditional financial services. With a focus on the transformation of the financial industry through technological innovation, this research explores the impact of Fintech in improving efficiency, accessibility and innovation. The literature review provides a clear understanding of key concepts, such as openness (Open Banking), financial security, operational efficiency, financial inclusivity, and user experience. Through a systematic literature review approach, this research investigates the implications of Fintech's transformation of traditional financial services and identifies emerging trends and challenges. Results and discussion include analysis of the impact of Fintech in improving financial services, solving existing problems, and providing a holistic perspective on paradigm shifts in the financial industry. The findings of this research contribute to a deep understanding of the evolution of Fintech and open space for further research in optimizing the benefits of financial technology for society and the global economy.